Kajian Syirik dan Tauhid dalam Perspektif al-Qur'an dan Hadis - Maslahah (Moderasi : Journal of Islamic Studies, 2021)
History records the destruction committed by the earlier people originated from the human belief that the creator of the universe was God. However, after creating this nature. He either gives up to be managed by some of His creatures, or they do so automatically, even without His permission. As mentioned, they believe that this management of nature is carried out by many parties, such as the angels, who are believed to be the daughters of God. It is, of course, a shirk, and the deed does not harm Allah Almighty and must be straightened out. The method of writing this article is qualitative. The author summarizes the opinions of the relevant previous research, compares them, and draws conclusions based on the Qur'an and hadith. Shirk is to associate Allah with something in uluhiyah, rububiyah or ubudiyah. Shirk usually comes from man's folly in thinking or obedience to satan worshipping creatures such as the sun, moon, and angels, likening God to other beings, and considering God to have children or wives. Among the consequences of shirking is that the sin is not forgiven. Meanwhile, tawhid is the worship of Allah, the opposite of shirking. Tawhid is divided into three, Tauhid Rububiyah is still limited to recognition, while tauhid Uluhiyah and Asma wa Sifat have taken the form of amaliyah as a logical consequence of Uluhiyah. Shirk means to assume there are other forces apart from God, classic examples such as the worships above. We can analogize with the standard now because the essence of hypocrisy remains the same all the time.